IMPROVING THE STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURE TEXT THROUGH NUMBERED HEADS TOGETHER TECHNIQUE - Evi Ramini; Elia Masa Gintings (Universitas Negeri Medan, 2012)
ABSTRACT This study attempts to improve students’ achievement in writing procedure text through Numbered Heads Together Technique. This study was conducted by using classroom action research. The subject of the research was class IX/A SMP SWASTA UPMI MEDAN that consisted of 30 students. The research was conducted in two cycles and the first cycle consisted of four meetings and the second cycle consisted of two meetings. The instruments of collecting data were quantitative data (Writing Test) and Qualitative data (diary notes, observation sheet, interview and questionnaire sheet). Based on the writing test score, students’ score kept improving in every test. In the test I the mean was 67,6, in the test II the mean was 74.5 and the test III the mean was 86.56. Based on observation sheet and questionnaire sheet, it was found that teaching learning process ran well. Students were active and interest in writing. The result of the research showed that NHT can improve students’ achievement in writing procedure text. Key Words: Writing, Procedure Text, Number Heads Together